Listening Comprehension Challenges Among University English Majors: Barriers and Pedagogical Solutions - Nofry Frans; Vera Wahani (CV. Edujavare Publishing, 2026)
Listening comprehension is a fundamental receptive skill that supports the development of overall English language proficiency among university students. However, many English majors continue to experience significant difficulties in understanding spoken English due to the interaction of linguistic, cognitive, psychological, and pedagogical factors. Although previous studies have examined these issues independently, a comprehensive synthesis that integrates the various challenges and pedagogical solutions remains limited. Therefore, this study aims to review and synthesize the existing literature on listening comprehension challenges among university English majors and to identify effective pedagogical strategies for improving listening instruction in higher education. This study employed a narrative literature review approach by analyzing scholarly publications from reputable national and international journals, books, and related academic sources published between 2015 and 2025, complemented by seminal theoretical references. The collected literature was analyzed using thematic analysis to identify recurring issues, compare research findings, and develop a comprehensive conceptual understanding of listening instruction. The findings reveal that listening comprehension difficulties are influenced by three major dimensions: linguistic barriers, including vocabulary limitations, grammar, pronunciation, and accent variation; cognitive and psychological barriers, including limited working memory, listening anxiety, motivation, self-confidence, and background knowledge; and pedagogical barriers related to instructional strategies, learning media, authentic materials, assessment, and classroom environments. The review further highlights that integrating metacognitive listening strategies, bottom-up and top-down processing, extensive and intensive listening, task-based learning, collaborative learning, scaffolding, and technology-enhanced instruction can significantly improve students' listening comprehension. This review contributes by proposing an integrated conceptual framework that may guide future research and support more effective listening instruction in higher education.